PERAN FIGUR AYAH DAN IBU DALAM MEMBENTUK KEMAMPUAN PENGENDALIAN EMOSI PADA ANAK - Nurhayani Nurhayani (JURNAL TARBIYAH, 2014)
Every child has an unic and special characteristic which are different from their peers. The differences in emotional development need to get special care so they can regulate their emotion properly, especially Special children need to be understood that their difficulties to regulate emotion are not because of their will, but they need their parents encourage to make them sure about their effort to regulate their emotion that they feel. Parents’ confidence and figure models that were observed in family contribute in shaping their children’s self confidence to regulate their emotion and encourage them can be independent and be brave take a risk; so they can behave properly in social environment and can be avoided social adapting problems in their life.